Despite delayed kinetics, people living with HIV achieve equivalent antibody function after SARS-CoV-2 infection or vaccination - Motsoeneng, Boitumelo M.; Manamela, Nelia P.; Kaldine, Haajira; Kgagudi, Prudence; Hermanus, Tandile; Ayres, Frances; Makhado, Zanele; Moyo-Gwete, Thandeka; van der Mescht, Mieke A.; Abdullah, Fareed; Boswell, Michael T.; Ueckermann, Veronica; et al. (Frontiers in Immunology, 2023)
Abstract The kinetics of Fc-mediated functions following SARS-CoV-2 infection or vaccination in people living with HIV (PLWH) are not known. We compared SARS-CoV-2 spike-specific Fc functions, binding and neutralization in PLWH and people without HIV (PWOH) during acute infection (without prior vaccination) with either the D614G or Beta variants of SARS-CoV-2, or vaccination with ChAdOx1 nCoV-19. Antiretroviral treatment (ART)-naïve PLWH had significantly lower levels of IgG binding, neutralization and antibody-dependent cellular phagocytosis (ADCP) compared with PLWH on ART. The magnitude of antibody-dependent cellular cytotoxicity (ADCC), complement deposition (ADCD) and cellular trogocytosis (ADCT) were differentially triggered by D614G and Beta. The kinetics of spike IgG binding antibodies, ADCC and ADCD were similar, irrespective of the infecting variant, between PWOH and PLWH overall. However, compared with PWOH, PLWH infected with D614G had delayed neutralization and ADCP. Furthermore, Beta infection resulted in delayed ADCT, regardless of HIV status. Despite these delays, we observed improved coordination between binding and neutralizing responses and Fc functions in PLWH. In contrast to D614G infection, binding responses in PLWH following ChAdOx-1 nCoV-19 vaccination were delayed, while neutralization and ADCP had similar timing of onset, but lower magnitude, and ADCC was significantly higher than in PWOH. Overall, despite delayed and differential kinetics, PLWH on ART develop comparable responses to PWOH, supporting the prioritization of ART rollout and SARS-CoV-2 vaccination in PLWH.